Production function analysis of hulbot-hulbot fishing in Guimaras Strait and adjacent waters. - Ramos, Marjorie
This paper analyzed the productivity of hulbot-hulbot fishing in Guimaras Strait and adjacent waters. This study used portion of the generated data by Padilla et al. (1990) in the Asian Fisheries Social Science Research Ntework (AFSSRN)-University of the Philippines in the Visayas (UPV) Team entitles, "The Fishery Resource System for Small Pelagic Fisheries of Guimaras Strait and Adjacent Waters." Padilla et. al. used purposive sampling technique. The study monitored data on catch, costs and earnings of 34 hulbot-hulbots every other week for the period October 1988 to November 1989., The production function approach using the Cobb-Douglas function a form used to explain the variations in the level of fish catch of hulbot-hulbot fishermen. Eight explanatory variables were included in the analysis : boat tonnage, mesh size, distance traveled, actual fishing time, labor costs, fuel, number of hauls and miscellaneous operating costs. Three variables, namely, actual fishing time, labor costs and fuel were found significantly affecting the level of fish catch. The F-statistic rejected the null hypothesis that the explanatory variables do not explain the variations in the level of fish catch. This implies that at least one of the explanatory variables affects the level of fish catch. Both labor cost and fuel were used inefficiently by the fishermen. The use of labor cost and fuel should be increased if profit is to be maximized.